2003
DOI: 10.1254/jphs.93.289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KRN4884, a Novel K+ Channel Opener, on Ionic Currents in Rabbit Femoral Arterial Myocytes

Abstract: Abstract. Effects of KRN4884 (5-amino-N-[2-(2-chlorophenyl)ethyl]-N'-cyano-3-pyridinecarboxamidine), a novel K + channel opener, on ionic currents were examined in rabbit femoral arterial myocytes (RFAMs). Under whole-cell clamp conditions where cells were superfused with 5.9 mM K + bathing solution, KRN4884 elicited an outward current at -30 mV. KRN4884-induced current had a reversal potential of -78 mV and was abolished by application of glibenclamide (glib). KRN4884 was approximately 43 times more potent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Animal studies have shown variable relaxation to KRN4884 depending on the animal and location of the vessels examined. Some groups report that KRN4884 is equipotent to cromakalim [31], whereas others found KRN4884 to be up to 43 times more potent than levocromakalim on ionic currents in rat femoral artery myocytes [20]. Furthermore, it has been reported that KRN4884 is a longer-lasting antihypertensive in spontaneously hypertensive rats compared to laevocromakalim [19,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have shown variable relaxation to KRN4884 depending on the animal and location of the vessels examined. Some groups report that KRN4884 is equipotent to cromakalim [31], whereas others found KRN4884 to be up to 43 times more potent than levocromakalim on ionic currents in rat femoral artery myocytes [20]. Furthermore, it has been reported that KRN4884 is a longer-lasting antihypertensive in spontaneously hypertensive rats compared to laevocromakalim [19,31].…”
Section: Discussionmentioning
confidence: 99%
“…KRN2391 has also been suggested to have dual modes of action; a K ATP channel opener and an organic nitrate [17,18] and, thus, may provide a more potent tool for placental vascular relaxation. Another Kirin compound, KRN4884, has also been reported to act as a K ATP channel opener, directly activating the channels and by decreasing the sensitivity of the channels to ATP [19][20][21][22]. However, there is no data in the literature detailing its effects on the nitric oxide pathway.…”
Section: Introductionmentioning
confidence: 99%
“…124) In contrast, the BK channel has consistently been an attractive drug target for the treatment of diseases due to smooth muscle hypercontractility, including hypertension, overactive bladder, incontinence, asthma, chronic obstructive pulmonary disease, and threatened premature labor. [138][139][140] Similar to ATP-sensitive K + channel openers, such as nicorandil, 141) minoxidil, 142) (levo) cromakalim 143,144) KRN2391, 145) and KRN4884, 146) the development of BK channel openers targeting these diseases has been extensively challenged, but not yet successful in clinical trials. 138,147) The main undesired effects of BK channel openers are facial flushing, migraine, and postural hypotension.…”
Section: -1 Bk Channel-related Diseases and Modulator Pharmacologymentioning
confidence: 99%